Formal Knowledge Examination Institutions: Chance Or Threat to European Medium Tech-Nology SMEs? A Cognitive and Institutional Perspective - Silviya Draganinska; Rudiger Wink (European Regional Science Association (ERSA), 2006)
For most SME in incumbent medium-technology sectors, international business is only possi-ble, if additional support by specified institutions is provided. These additional services in-clude information on foreign markets – regulation, market partners, sales potential – as well as coordination – for trade fairs, common international recruitment and qualification strategies – and capabilities like access to financial markets or international public funding for interna-tionalisation or cutting-edge technological knowledge. For many of these services, private provision is possible, as exclusive use and rivalry in consumption are given. For other ser-vices, however, network characteristics restrict a completely private provision. The proposed paper analyses institutional arrangements particularly designed on regional, national or European level to support linkages between organisations and networks in differ-ent European regions. The investigation is based on information collected within the frame-work of the "IKINET project – International Knowledge and Innovation Network" (EU FP6, N° CIT2-CT-2004-506242). The specific challenge of the institutions investigated within this paper refers to linkages between organisations and networks with different institutional de-signs, e.g. the role of public and/or private supply, the characteristics and subjects of services, organisational structures and modes of coordination. These institutions attempt to bridge the gap between SME and organisations in different regions, but also to ease the access to EU funding for transnational (transregional) cooperation between SME. The paper will analyse their products, organisational structure, funding and codes of interaction. This investigation will be used to identify general and regionally specific prerequisites for effective interregional boundary spanning institutions. Secondly, the connectivity between the institutions will be analysed to reveal necessary standards or institutional arrangements to secure interregional trust in cooperation. These standards can range from rather informal, for example on the basis of business norms in trade fairs, to completely formal arrangements, for example in the case of contractual agreements on intellectual property rights and licenses. The assessment of these institutional arrangements uses an integrative methodological framework based on institu-tional analysis to overcome information asymmetries in cooperative innovative processes, sociological and cognitive psychological models of organisational and cognitive proximity and management models for SME as learning organisations. As a result, insights are expected for the European Union, which institutional arrangements are necessary for technology plat-forms on a regional level to secure interregional knowledge interactions.
Keywords: 330